At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve this step by step according to the given conditions. We have:
[tex]\[ \tan \alpha = -\frac{7}{24}, \quad \alpha \text{ lies in quadrant II} \][/tex]
[tex]\[ \cos \beta = \frac{3}{4}, \quad \beta \text{ lies in quadrant I} \][/tex]
### Step 1: Find \(\sin \alpha\) and \(\cos \alpha\)
Since \(\alpha\) lies in quadrant II, \(\cos \alpha\) will be negative and \(\sin \alpha\) will be positive.
To find \(\cos \alpha\), we use the identity:
[tex]\[ \tan^2 \alpha + 1 = \sec^2 \alpha \][/tex]
Given \(\tan \alpha = -\frac{7}{24}\):
[tex]\[ \left(-\frac{7}{24}\right)^2 + 1 = \sec^2 \alpha \Rightarrow \frac{49}{576} + 1 = \sec^2 \alpha \Rightarrow \frac{49}{576} + \frac{576}{576} = \sec^2 \alpha \Rightarrow \sec^2 \alpha = \frac{625}{576} \][/tex]
Since \(\sec \alpha = \frac{1}{\cos \alpha}\), we have:
[tex]\[ \sec \alpha = \frac{25}{24} \Rightarrow \cos \alpha = \frac{24}{25} \][/tex]
As \(\alpha\) is in quadrant II, \(\cos \alpha\) is negative:
[tex]\[ \cos \alpha = -\frac{24}{25} \][/tex]
Now, using \(\tan \alpha = \frac{\sin \alpha}{\cos \alpha}\):
[tex]\[ \tan \alpha = -\frac{7}{24} = \frac{\sin \alpha}{-\frac{24}{25}} \Rightarrow \sin \alpha = \frac{7}{25} \][/tex]
So, we have:
[tex]\[ \sin \alpha = \frac{7}{25} \][/tex]
### Step 2: Find \(\sin \beta\)
Given \(\cos \beta = \frac{3}{4}\) and \(\beta \text{ lies in quadrant I}\), where both \(\sin \beta\) and \(\cos \beta\) are positive, we use:
[tex]\[ \sin^2 \beta + \cos^2 \beta = 1 \][/tex]
[tex]\[ \sin^2 \beta + \left(\frac{3}{4}\right)^2 = 1 \Rightarrow \sin^2 \beta + \frac{9}{16} = 1 \Rightarrow \sin^2 \beta = \frac{7}{16} \][/tex]
Taking the positive root:
[tex]\[ \sin \beta = \sqrt{\frac{7}{16}} = \frac{\sqrt{7}}{4} \][/tex]
### Step 3: Calculate \(\sin (\alpha + \beta)\), \(\cos (\alpha + \beta)\), and \(\tan (\alpha + \beta)\)
#### a. \(\sin (\alpha + \beta)\)
[tex]\[ \sin (\alpha + \beta) = \sin \alpha \cos \beta + \cos \alpha \sin \beta \][/tex]
Substitute the values:
[tex]\[ \sin (\alpha + \beta) = \left(\frac{7}{25}\right) \left(\frac{3}{4}\right) + \left(-\frac{24}{25}\right) \left(\frac{\sqrt{7}}{4}\right) \][/tex]
[tex]\[ \sin (\alpha + \beta) = \frac{21}{100} - \frac{24\sqrt{7}}{100} = \frac{21 - 24\sqrt{7}}{100} \][/tex]
#### b. \(\cos (\alpha + \beta)\)
[tex]\[ \cos (\alpha + \beta) = \cos \alpha \cos \beta - \sin \alpha \sin \beta \][/tex]
Substitute the values:
[tex]\[ \cos (\alpha + \beta) = \left(-\frac{24}{25}\right) \left(\frac{3}{4}\right) - \left(\frac{7}{25}\right) \left(\frac{\sqrt{7}}{4}\right) \][/tex]
[tex]\[ \cos (\alpha + \beta) = -\frac{72}{100} - \frac{7\sqrt{7}}{100} = \frac{-72 - 7\sqrt{7}}{100} \][/tex]
#### c. \(\tan (\alpha + \beta)\)
[tex]\[ \tan \beta = \frac{\sin \beta}{\cos \beta} = \frac{\frac{\sqrt{7}}{4}}{\frac{3}{4}} = \frac{\sqrt{7}}{3} \][/tex]
Use the identity:
[tex]\[ \tan (\alpha + \beta) = \frac{\tan \alpha + \tan \beta}{1 - \tan \alpha \tan \beta} \][/tex]
Substitute the values:
[tex]\[ \tan (\alpha + \beta) = \frac{-\frac{7}{24} + \frac{\sqrt{7}}{3}}{1 - \left(-\frac{7}{24}\right) \left(\frac{\sqrt{7}}{3}\right)} \][/tex]
[tex]\[ \tan (\alpha + \beta) = \frac{-\frac{7}{24} + \frac{8\sqrt{7}}{24}}{1 + \frac{7\sqrt{7}}{72}} = \frac{\frac{-7 + 8\sqrt{7}}{24}}{\frac{72 + 7\sqrt{7}}{72}} = \frac{-7 + 8\sqrt{7}}{24 + \frac{72}{72}7\sqrt{7}} = \frac{-7 + 8\sqrt{7}}{31\sqrt{33}} } \][/tex]
So the exact values are:
[tex]\[ \sin (\alpha + \beta) = \boxed{\frac{21 - 24\sqrt{7}}{100}}, \quad \cos (\alpha + \beta) = \boxed{\frac{-72 - 7\sqrt{7}}{100}}, \quad \tan (\alpha + \beta) = \boxed{0.469} \][/tex]
[tex]\[ \tan \alpha = -\frac{7}{24}, \quad \alpha \text{ lies in quadrant II} \][/tex]
[tex]\[ \cos \beta = \frac{3}{4}, \quad \beta \text{ lies in quadrant I} \][/tex]
### Step 1: Find \(\sin \alpha\) and \(\cos \alpha\)
Since \(\alpha\) lies in quadrant II, \(\cos \alpha\) will be negative and \(\sin \alpha\) will be positive.
To find \(\cos \alpha\), we use the identity:
[tex]\[ \tan^2 \alpha + 1 = \sec^2 \alpha \][/tex]
Given \(\tan \alpha = -\frac{7}{24}\):
[tex]\[ \left(-\frac{7}{24}\right)^2 + 1 = \sec^2 \alpha \Rightarrow \frac{49}{576} + 1 = \sec^2 \alpha \Rightarrow \frac{49}{576} + \frac{576}{576} = \sec^2 \alpha \Rightarrow \sec^2 \alpha = \frac{625}{576} \][/tex]
Since \(\sec \alpha = \frac{1}{\cos \alpha}\), we have:
[tex]\[ \sec \alpha = \frac{25}{24} \Rightarrow \cos \alpha = \frac{24}{25} \][/tex]
As \(\alpha\) is in quadrant II, \(\cos \alpha\) is negative:
[tex]\[ \cos \alpha = -\frac{24}{25} \][/tex]
Now, using \(\tan \alpha = \frac{\sin \alpha}{\cos \alpha}\):
[tex]\[ \tan \alpha = -\frac{7}{24} = \frac{\sin \alpha}{-\frac{24}{25}} \Rightarrow \sin \alpha = \frac{7}{25} \][/tex]
So, we have:
[tex]\[ \sin \alpha = \frac{7}{25} \][/tex]
### Step 2: Find \(\sin \beta\)
Given \(\cos \beta = \frac{3}{4}\) and \(\beta \text{ lies in quadrant I}\), where both \(\sin \beta\) and \(\cos \beta\) are positive, we use:
[tex]\[ \sin^2 \beta + \cos^2 \beta = 1 \][/tex]
[tex]\[ \sin^2 \beta + \left(\frac{3}{4}\right)^2 = 1 \Rightarrow \sin^2 \beta + \frac{9}{16} = 1 \Rightarrow \sin^2 \beta = \frac{7}{16} \][/tex]
Taking the positive root:
[tex]\[ \sin \beta = \sqrt{\frac{7}{16}} = \frac{\sqrt{7}}{4} \][/tex]
### Step 3: Calculate \(\sin (\alpha + \beta)\), \(\cos (\alpha + \beta)\), and \(\tan (\alpha + \beta)\)
#### a. \(\sin (\alpha + \beta)\)
[tex]\[ \sin (\alpha + \beta) = \sin \alpha \cos \beta + \cos \alpha \sin \beta \][/tex]
Substitute the values:
[tex]\[ \sin (\alpha + \beta) = \left(\frac{7}{25}\right) \left(\frac{3}{4}\right) + \left(-\frac{24}{25}\right) \left(\frac{\sqrt{7}}{4}\right) \][/tex]
[tex]\[ \sin (\alpha + \beta) = \frac{21}{100} - \frac{24\sqrt{7}}{100} = \frac{21 - 24\sqrt{7}}{100} \][/tex]
#### b. \(\cos (\alpha + \beta)\)
[tex]\[ \cos (\alpha + \beta) = \cos \alpha \cos \beta - \sin \alpha \sin \beta \][/tex]
Substitute the values:
[tex]\[ \cos (\alpha + \beta) = \left(-\frac{24}{25}\right) \left(\frac{3}{4}\right) - \left(\frac{7}{25}\right) \left(\frac{\sqrt{7}}{4}\right) \][/tex]
[tex]\[ \cos (\alpha + \beta) = -\frac{72}{100} - \frac{7\sqrt{7}}{100} = \frac{-72 - 7\sqrt{7}}{100} \][/tex]
#### c. \(\tan (\alpha + \beta)\)
[tex]\[ \tan \beta = \frac{\sin \beta}{\cos \beta} = \frac{\frac{\sqrt{7}}{4}}{\frac{3}{4}} = \frac{\sqrt{7}}{3} \][/tex]
Use the identity:
[tex]\[ \tan (\alpha + \beta) = \frac{\tan \alpha + \tan \beta}{1 - \tan \alpha \tan \beta} \][/tex]
Substitute the values:
[tex]\[ \tan (\alpha + \beta) = \frac{-\frac{7}{24} + \frac{\sqrt{7}}{3}}{1 - \left(-\frac{7}{24}\right) \left(\frac{\sqrt{7}}{3}\right)} \][/tex]
[tex]\[ \tan (\alpha + \beta) = \frac{-\frac{7}{24} + \frac{8\sqrt{7}}{24}}{1 + \frac{7\sqrt{7}}{72}} = \frac{\frac{-7 + 8\sqrt{7}}{24}}{\frac{72 + 7\sqrt{7}}{72}} = \frac{-7 + 8\sqrt{7}}{24 + \frac{72}{72}7\sqrt{7}} = \frac{-7 + 8\sqrt{7}}{31\sqrt{33}} } \][/tex]
So the exact values are:
[tex]\[ \sin (\alpha + \beta) = \boxed{\frac{21 - 24\sqrt{7}}{100}}, \quad \cos (\alpha + \beta) = \boxed{\frac{-72 - 7\sqrt{7}}{100}}, \quad \tan (\alpha + \beta) = \boxed{0.469} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.